(untitled) (Journal of Universal Science Research, 2023)
The foreach loop is primarily designed to make working with arrays and collection values easier, allowing you to refer to each element of an array without knowing the number of elements in it. The foreach statement: enumerates the elements of a collection and executes its body for each element of the collection. This article discusses the foreach operator and how to write programs using this operator, test and execute different parts of the code based on test results.